Evolução da Hepatite C em pacientes submetidos a transplante hepático: estudo clínico-laboratorial com ênfase na recorrência da Hepatite C pós-transplante - Erica de Oliveira Godinho (2006)
A clinical, descriptive study was conducted at the Transplantation Unit of the Gastroenterology Alfa Institute Hospital das Clínicas da Universidade Federal de Minas Gerais - , in order to investigate the clinical, biochemical and histological follow-up (with special attention to graft recurrence of hepatitis C) of patients who undergone a liver transplantation at the Service, due to hepatic insuficiency secondary to chronic hepatitis C (with or without other associated hepatocelular injury factors). From september 1994 to december 2003 (period studied), 218 liver transplantations were carried out, of those 59 were in patients with cirrhosis due to chronic hepatitis C. Among this 59 patients, 42 were alive at the occasion of this research, and it was possible to study 36 of them. The effect of numerous pre-, intra- and post-operative variables in the follow-up of this patients after liver transplantation was investigated. The variables considered were: pre-operative demografic caracteristics (sex and age of patients), risk factors for hepatitis C infection (previous history of blood transfusion, of intravenous drugs use, of sexual promiscuity, and of previous surgical procedures), presence of other diseases able to induce hepatocelular injury (alcoholism, obesity, hepatic steatosis, diabetes mellitus 1 and 2, iron overload states, hepatitis B virus coinfection, and end stage renal failure), viral factors (genotype, viral load), antiviral treatment for hepatitis C; intra-operative year in which the transplantation occurred, hot and cold ischemia period, hemotransfusion during the surgery (red blood cells, platelets, frozen plasma, crioprecipitated), surgical complications (hepatic artery thrombosis, hepatic artery stenosis, stenosis of biliar ducts, biliar fistules); post-operative- immunossupression protocols, citomegalovirus infection, acute rejection, recurrence of thehepatitis C in the allograft. Special attention was given, in this study, to this last variable, and its association with all the other variables was analysed. Previous history of blood transfusion was the only variable found to be associated, in a statistically significant way (p = 0,019), to the graft recurrence of hepatitis C. This fact seems, although, to be inespecific. Patients showed a milder pattern of recurrence despite all limitations to early diagnosis. No trend towards a higher number of cases of recurrent hepatitis C in patients submited to hepatic transplantation in last years was observed. No relationship between transaminases rising and histologic follow-up of the allograft after liver transplantation was found, as there was no protocol for serial biopsies. There were numerous obstacles to the proposes of the study, such as unavailability of kits for specific tests (HCV genotype and viral load, diagnosis of citomegalovirus infection), the absence of a protocol for serial biopsies after liver transplantation in the Service where the study was conducted, the modifications of immunossupression protocols throughout the period studied, etc. This study leaves, as many others available in the international literature, many points to be explained, which must encourage new studies, aiming for a better knowledge of the natural history of hepatitis C after liver transplantation.